ISOLATION AND CHARACTERIZATION OF HYDROCARBON DEGRADING BACTERIA IN CRUDE OIL POLLUTED SOIL IN THE NIGER DELTA - MANSI, EGBO W.; AKARANTA, PROF ONYEWUCHI; ABU, PROF GIDEON (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
Bioremediation as pollution remediation technique takes advantage of the ability of some microorganisms to degrade organic matter in the environment. Bacteria are important group of microorganism that plays key role in the bioremediation process. Bacteria are ubiquitous organisms that inhabit soil water and air matrices. In this study, some hydrocarbon degrading bacteria have been isolated and identified by morphological and biochemical methods.. Eight different hydrocarbon degrading bacteria were isolated from crude polluted soil collected from oil spill site in Ikarama community in Yenagoa Local Government Area of Bayelsa State in the Niger Delta. The total population of heterotrophic bacterium enumerated per gram of each soil sample are 1.42x107 , 1.7x107 and 3.1x108 for location 1,2 and 3 respectively While population of total hydrocarbon degrading bacteria enumerated are 4.2x106 , : 3.7x106 and 1.43x106 for location 1, 2 and 3 respectively. This population of hydrocarbon degrading bacteria in the soil is enough to initiate natural biodegradation of crude oil pollutant. With the right environmental conditions for the bacteria, bioremediation can be effectively deployed to remediate the spilled area.